2011
DOI: 10.1002/pits.20547
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐behavioral therapy in the schools: Bringing research to practice through effective implementation

Abstract: A number of evidence-based, cognitive-behavioral interventions have been developed that are appropriate for use with children and adolescents in school settings. Despite the potential for these interventions to prevent or ameliorate a number of child and adolescent mental health problems, their use in schools remains low. Literature related to implementation of new programs indicates that personal, social, and organizational factors influence implementation success. What is known in general about implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…In addition to organization factors, there is an interaction between the organization and both characteristics of an intervention and of its implementer (Forman & Barakat, 2011). These interactions are referred to as the intervention-setting fit, compatibility, or appropriateness (Proctor et al, 2011; Rogers, 2003).…”
Section: Contextual Issuesmentioning
confidence: 99%
“…In addition to organization factors, there is an interaction between the organization and both characteristics of an intervention and of its implementer (Forman & Barakat, 2011). These interactions are referred to as the intervention-setting fit, compatibility, or appropriateness (Proctor et al, 2011; Rogers, 2003).…”
Section: Contextual Issuesmentioning
confidence: 99%
“…Factors related to the implementation may be as important as the selection of an appropriate evidence‐based SBI. Forman and Barakat () extracted five factors influencing the implementation of new programmes in the school setting:…”
Section: Implementing Sbimentioning
confidence: 99%
“…However, despite the recognition of the importance of teacher PD, the literature reports that the state of teachers' PD is still inadequate (Lawless & Pellegrino, 2007). There is an emerging research base on school-based implementation that pinpoints specific methods of increasing the uptake and use of evidence-based practices that address students' social, emotional, behavioural needs (Forman & Barakat, 2011). Studies on intervention implementation have demonstrated that the 'train and hope' philosophy of most PD efforts does not result in effective implementation and positive outcomes (Fixsen, Naoom, Blase, Friedman, & Wallace, 2005).…”
Section: Professional Development and Coachingmentioning
confidence: 99%